2002
DOI: 10.1002/j.2161-007x.2002.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Counseling: What Do Counseling Students Think About It?

Abstract: The author discusses students' reactions to 4 seminars. 1‐hour each, on the topic of spirituality in counseling. Students were enrolled in a master's‐level counseling program, Several issues emerged that have implications for the training of counselors on spiritual issues, including students' level of comfort with discussing spiritual issues, the difficulty of defining spirituality, client and counselor readiness to explore spirituality, and training issues in the area of spirituality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
54
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 16 publications
3
54
0
1
Order By: Relevance
“…Manevi gelişimi korumanın yararları hakkında literatürde artan desteğe rağmen, kilise ve devlet ayrımının yasal zorunlulukları, ahlaki kuralları, bireysel değerleri, bilgi ve ehliyetine bağlılık, okul psikolojik danışmanlarının manevi ve dini konuları okullarda ele almaktaki rahatlık düzeylerini hala etkilemektedir (Lambie vd., 2008;Sink & Richmond, 2004;Young vd., 2002). Ek olarak psikolojik danışma öğrencileri yargılanma ve diğerle-rine karşı saldırgan olarak anlaşılma korkusunun, kendilerinde maneviyat konularının tartışılmasından rahatsız olma duyguları oluşmasına neden olduğunu bildirmiştir (Souza, 2002). Bu faktörlere rağmen, alan yazınında kilise ve devletin ayrımını koruyarak ve ahlaki kurallara bağlı kalarak maneviyatı okul psikolojik danışma programlarına entegre etmenin olası olduğuna dair yeterli destek mevcuttur (Allen & Coy, 2004;Lambie vd., 2008;MacDonald, 2004;Sink, 2004).…”
unclassified
“…Manevi gelişimi korumanın yararları hakkında literatürde artan desteğe rağmen, kilise ve devlet ayrımının yasal zorunlulukları, ahlaki kuralları, bireysel değerleri, bilgi ve ehliyetine bağlılık, okul psikolojik danışmanlarının manevi ve dini konuları okullarda ele almaktaki rahatlık düzeylerini hala etkilemektedir (Lambie vd., 2008;Sink & Richmond, 2004;Young vd., 2002). Ek olarak psikolojik danışma öğrencileri yargılanma ve diğerle-rine karşı saldırgan olarak anlaşılma korkusunun, kendilerinde maneviyat konularının tartışılmasından rahatsız olma duyguları oluşmasına neden olduğunu bildirmiştir (Souza, 2002). Bu faktörlere rağmen, alan yazınında kilise ve devletin ayrımını koruyarak ve ahlaki kurallara bağlı kalarak maneviyatı okul psikolojik danışma programlarına entegre etmenin olası olduğuna dair yeterli destek mevcuttur (Allen & Coy, 2004;Lambie vd., 2008;MacDonald, 2004;Sink, 2004).…”
unclassified
“…Souza (2002) as well as Horfman & Walach (2011) stated that the application of the religious or spiritual aspect coincides with the importance of diversity in counseling and it is essential that a counselor understands the spiritual aspect as an aspect of client diversity. Day (2010) explained, "A body of recent research has noted some positive impact of spirituality on well-being.…”
mentioning
confidence: 99%
“…C urrently, significant national attention is being paid to the role of spirituality in people's mental health and well-being (Bullis, 1996;Favier, Engersoll, O'Brien, & McNally, 2001;Fukuyama & Sevig, 1999, 2002Kelly, 1995;W. R. Miller, 1999;Richards & Bergin, 1997, 2000Sperry & Shafranske, 2005).…”
mentioning
confidence: 99%
“…For example, a survey of college counselors found that more than 70% were open to the discussion and use of the topics of religion and spirituality in counseling (Weinstein, Parker, & Archer, 2002). Also students in counseling programs have supported the need for training in this area (Souza, 2002).…”
mentioning
confidence: 99%